Scenarios for Small and Medium Enterprises (Smes) Provisions in the North American Free Trade Agreement (Nafta) Renegotiation: a Critical Analysis of Challenges and Opportunities - Vargas Hernández, José (2018)
The aim of this paper is to set some scenarios for small and medium enterprises (SMEs) from a critical analysis of the provisions in the North American Free Trade Agreement (NAFTA) renegotiation, its challenges and opportunities. The critical analysis departs from the questionable position of the withdrawal from NAFTA and their consequences for SMEs of not giving continuity through a process of renegotiation among the three partners. The method used is the critical analysis based mainly in some sources of information, analysis of results of NAFTA, and the strategic examination of its challenges and opportunities for SMEs. Finally, the analysis establish some possible scenarios post-NAFTA renegotiation and some strategic proposals for the SMEs.